H2-rich syngas from glycerol dry reforming over Ni-based catalysts supported on alumina from aluminum dross - Nurul Asmawati, Roslan; Sumaiya, Zainal Abidin; Osazuwa, Osarieme Uyi; Chin, Sim Yee; Y. H., Taufiq-Yap (Elsevier Ltd, 2021)
The performance of Ni-based catalyst supported on γ-Al2O3 for glycerol dry reforming (GDR) reaction was investigated in the current study. γ-Al2O3 was prepared from aluminum dross (AD) before use as catalyst support. Al2O3 was extracted using three different techniques assisted with ultrasonication: acid leaching with ammonia precipitation, acid leaching with re-precipitation of HCl, and alkaline leaching with ammonium hydrogen carbonate. The results show that extracted γ-Al2O3 3 (EGA3) with the highest purity and the surface area of 267.5 m2 g−1 was produced from acid leaching with ammonia precipitation technique at a calcination temperature of 800 °C. A series of Ni/EGA3 (5%, 10%, 15% and 20%) catalysts were tested and it was found that the catalytic activity was increased in the order of 5%Ni/EGA3 < 10%Ni/EGA3 < 20%Ni/EGA3 < 15%Ni/EGA3. 15%Ni/EGA3 catalyst has the highest catalytic activity due to the excellent distribution of Ni on the EGA support, high specific surface area of the support and high catalyst's basicity. In addition, the strong Ni-EGA3 interaction of the 15%Ni/EGA3 catalyst suppressed the carbon formation with the catalyst having the lowest carbon deposition value of 25.51% during the GDR reaction carried out for 8 h. Studies on the GDR reaction catalytic activities revealed that 15%Ni/EGA3 achieved the maximum catalytic activity with 56.7% glycerol conversion, 44.7% H2 yield, and 40.6% CO yield at 800 °C and CGR of 1:1. The H2:CO ratio obtained in this study was approximately 1.2–1.5 throughout the reaction, depicting a relatively rich H2 syngas product. Overall, the strong interaction between Ni and EGA3 ensured stable Ni particles that can mitigate carbon deposits, thereby enhancing the catalytic activity.